Implementasi EDM dan E-RKAM di Madrasah Ibtidaiyah Muhammadiyah Tanjungsari - Abdul Fitri Berlianto; Laila Wulandari (Universitas Islam Negeri Walisongo, 2022)
This study aims to get an overview of the implementation of EDM and E-RKAM in Madrasah Ibtidaiyah Muhammadiyah Tanjungsari Banyudono. This study uses a qualitative method where all information obtained from observations, documents and interviews is described in the form of written narratives as findings in the field. The results of the study illustrate that the implementation of EDM and E-RKAM is going well. The stages passed are also in accordance with the guidelines from the Ministry of Religion of the Republic of Indonesia, namely forming a TEAM, conducting socialization, collecting data and information, discussing and setting the level of each indicator, filling out instruments available online or semi-online, the Madrasah Head approves the results of the EDM fields, send EDM filling results. The results of the EDM will be used as material for determining priority types of programs/activities in preparing plans for the improvement and development of madrasas as outlined in the E-RKAM. The benefits of implementing EDM and E-RKAM include: knowing the strengths, weaknesses and challenges that madrasas have, knowing opportunities to improve the quality of education, knowing the types of needs needed to improve the quality of education, knowing the level of achievement of madrasah performance, being able to identify priority programs/activities for improving madrasah performance.